TEM and XPS studies on the faceted nanocrystals of Ce0.8Zr0.2O2 - Prusty D.; Pathak A.; Mukherjee M.; Mukherjee B.; Chowdhury A. (My University, 2025)
Faceted nanocrystals of Ce0.8Zr0.2O2 synthesised by co-precipitation method were characterised by X-ray diffraction, high-resolution transmission electron microscopy, thermogravimetry-differential scanning calorimetry and X-ray photoelectron spectroscopy techniques. The nanocrystals were highly faceted and exhibited a cubic phase. X-ray photoelectron spectroscopy analyses confirmed the presence of vacancy related defects and revealed the presence of ~ 22% of Ce3 + in the nanopowders. High-resolution transmission electron microscopy results confirmed that the nanocrystal sizes are around 31 ± 5 nm and the obtained hexagonal cross-section shape is bound by hexagonal {111} and square {100} facets. The shape-controlled nanocrystals were synthesised without using any surfactants or complexing agents and retained their morphology beyond 800 °C. This is a simple and easy method for producing shape-controlled Ce0.8Zr0.2O2 nanoparticles which can be used for catalytic conversion and other related advanced technological areas. © 2014 Published by Elsevier Inc.